Flouting Maxim of Relevance: A Pragmatic Analysis of Main Characters’ Dialogues in “Inside Out 2” Movie - Ni Kadek Saina Dayabhi; Komang Dian Puspita Candra (Universitas Islam Negeri Palopo, 2025)
Pragmatics is essential for understanding implied meaning beyond literal language in cinematic dialogues, providing valuable insights into character interaction and story development. This study explores the deliberate flouting of the maxim of relevance, based on Grice’s (1975) Cooperative Principle, in the animated film Inside Out 2. Using a qualitative descriptive method, data were collected through careful observation and verbatim transcription of 58 dialogue exchanges. Among these, 21 instances of maxim of relevance flouting were identified, with eight selected for detailed examination. The analysis reveals that these pragmatic strategies serve to express hidden meanings, regulate emotions, and navigate complex interpersonal relationships between characters. These communicative choices uncover psychological depth and enhance both character development and plot progression. Uniquely, this research contributes to pragmatic theory by examining conversational relevance manipulation within animation, expanding film studies scholarship. The findings also offer practical implications for language education and media analysis by demonstrating how pragmatic competence enriches understanding of dialogue in multimedia contexts.